The union makes us strong : an exhibition of trade union banners, badges and emblems - Simon, Dave (ACTSS (Association of Clerical, Technical and Supervisory Staff) / T&GWU (Transport and General Workers' Union), 1978)
Artwork by David Simon; black and white photograph of demonstration, coloured with red, blue and yellow; large banner at the centre says 'The union makes us strong' Poster advertising exhibition of trade union banners, badges and emblems, 1800-1978, held at the Fruit Market Gallery, Edinburgh, 16 December-27 January, 1978 PO-0190